Effect of work environment, quality of system and work culture on satisfaction of accounting information system user - Mandala, I Gusti Ngurah Agung Kepakisan; Astika, Ida Bagus Putra (International research journal of management, IT and social sciences, 2019)
The purpose of this study to explain the empirical evidence of the influence of the work environment, the quality of IT systems and work culture on the satisfaction of users of accounting information systems at PT XYZ. Sampling in this study uses nonprobability sampling methods that use criteria that employees who are sampled are employees using IT systems in his work with saturated sampling techniques, data was collected using a survey method with questionnaire techniques with respondents were employees at PT XYZ by analyzing the data using multiple linear regression. 216 questionnaires were distributed but only 124 questionnaires could be processed. The research results show that the work environment influences the satisfaction of cash system users, IT system quality influences the satisfaction of cash system users and work culture influences the satisfaction of cash system users. The results of hypothesis testing provide a synthesis that the better the work environment, the quality of IT systems and work culture, then the satisfaction of cash system users produced by employees at PT XYZ will be better too.